2020
DOI: 10.1186/s12889-020-08913-0
|View full text |Cite
|
Sign up to set email alerts
|

Design and psychometric properties of a questionnaire to assess gender sensitivity of perinatal care services: a sequential exploratory study

Abstract: Background Providing gender sensitive reproductive health service is recently emphasized by health organizations. This study aims to develop and assess psychometric properties of a questionnaire to assess gender sensitivity of perinatal care services (GS-PNCS) to be used by managers of perinatal services. Methods This study is a mixed sequential (Qualitative-Quantitative) exploratory study. In the qualitative phase, 34 participants were interviewed and the items were generated. To evaluate the validity; face,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…It should be also noted that male involvement is not only helping to promote maternal-neonatal health but also is the main stage for paternal adaptation [ 26 ] and improves men’s health as well [ 25 ]. Therefore, paternal health and counseling services should be integrated into maternal-infant health services, and providing gender-based health services are strongly recommended for any society [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be also noted that male involvement is not only helping to promote maternal-neonatal health but also is the main stage for paternal adaptation [ 26 ] and improves men’s health as well [ 25 ]. Therefore, paternal health and counseling services should be integrated into maternal-infant health services, and providing gender-based health services are strongly recommended for any society [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies showed that these services not only help them to adapt to paternal roles [ 26 , 27 ] but also are effective in ensuring maternal-fetal and -neonatal health [ 28 , 29 ]. Besides, recent studies have emphasized providing gender-based care and counseling services, especially based on the men’s needs in perinatal care and breastfeeding programs, to improve the quality of the services [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be also noted that, male involvement is not only helps to promote maternal-neonatal health but also is a main stage for paternal adaptation (33) and also helps to improve men's health (25). So, maternal-infant health services should be integrated with paternal services and gender based health needs for any society (34).…”
Section: Discussionmentioning
confidence: 99%
“…This group then used a ve-round Delphi technique [50]. The rst panel examined the item face validity per subdimension [51]. Second, members of the second panel, consisting of 13 senior hospital executives from four Palestinian hospitals, were asked to assess the importance of 45 subdimensions to the strategic development of hospitals on a 10-point semantic scale.…”
Section: Item and Scale Generationmentioning
confidence: 99%